2020
DOI: 10.1364/ome.411432
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Ag2S/SiO2 core/shell quantum dots with IR luminescence

Abstract: This paper presents the results of studies of the luminescent properties for colloidal Ag2S quantum dots, coated with SiO2 shell, carried out by techniques of transmission electron microscopy, optical absorption and luminescence spectroscopy time correlated single photon counting, quantum yield of luminescence. Various approaches to the formation of SiO2 shell is analyzed. It is concluded that an increase in the quantum yield of Ag2S QDs luminescence in the condition of the formation of a SiO2 shell on the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
1
9
0
2
Order By: Relevance
“…It is observed that the ratio of trap emission decreases under high shelling temperature to some extent, especially for samples prepared with ZnI 2 and ZnBr 2 . In addition, the radiative and nonradiative recombination constants ( k r and k nr , respectively) can be obtained by combining the results of TRPL and PLQY measurements, [ 47 ] which are listed in Table S4, Supporting Information. It is obvious that the k r becomes larger and k nr decreases with shelling temperature increasing, which confirms the high shelling temperature induces the reduction of nonradiative recombination for all samples.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the ratio of trap emission decreases under high shelling temperature to some extent, especially for samples prepared with ZnI 2 and ZnBr 2 . In addition, the radiative and nonradiative recombination constants ( k r and k nr , respectively) can be obtained by combining the results of TRPL and PLQY measurements, [ 47 ] which are listed in Table S4, Supporting Information. It is obvious that the k r becomes larger and k nr decreases with shelling temperature increasing, which confirms the high shelling temperature induces the reduction of nonradiative recombination for all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the small particle size, the probability for defect to localize near the nanoparticle boundary is high. An electron excited inside a defect can be captured by surface functional groups, dangling bonds, and traps. Electron trapping induces a dipole moment in the particle, which makes further excitation and emission of the defect impossible, until the electron is released from the trap and the surface state is empty. Such charged states can also affect dipole transitions of the defect.…”
Section: Resultsmentioning
confidence: 99%
“…There is a direct relationship between the duration of silanization and the thickness of the SiO 2 layer for quantum dot@silica composites, which probably can be explained by the low porosity of quantum dots [42]. The shell thickness can be varied from 1 to 25 nm depending on the initial quantum dot size [43], and the typical duration for stable SiO 2 shell condensation is no less than 20-24 h [42,44,45]. In the case of highly porous nanoparticles, the dependence may be nonlinear, as we demonstrated.…”
Section: Figurementioning
confidence: 99%